Роль ШІ у розробці інтерактивних вправ та онлайн-тестів з англійської мови - Коляда, Ірина Валеріївна; Косточка, Ігор Володимирович (Університет Григорія Сковороди в Переяславі, 2025)
The article examines the role of artificial intelligence (AI) – in particular large language models such as ChatGPT – in opening up new horizons in educational activities, in particular in English language teaching. It allows the creation of interactive exercises, online tests and adaptive learning resources that meet the needs of modern students. In this article, we will explore key aspects of the application of AI in the development of language tasks, the assessment of its effectiveness, challenges and prospects.
Keywords: assessment; artificial intelligence; innovative means; intelligent learning systems; native speakers; phenomenon